2016
DOI: 10.1007/s11892-016-0750-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Abnormalities in Youth with Obesity and Type 2 Diabetes

Abstract: Childhood obesity has been linked to cardiovascular disease (CVD) risk in adulthood. Of great concern is the expected increase in the population's CVD burden in relation to childhood obesity. This is compounded by the risk related to chronic hyperglycemia exposure in youth with type 2 diabetes. We herein provide an overview of the spectrum of early cardiovascular disease manifestation in youth with obesity and type 2 diabetes, in particular abnormalities in cardiac structure and function. Cardiac remodeling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 115 publications
0
47
0
1
Order By: Relevance
“…Chronic proinflammatory cytokines are considered to be pathologic mediators of diabetogenic metabolic disorders, associated with insulin resistance and pancreatic islet cell death [8][9][10]21,22]. Recent studies have shown the participation of inflammasome complexes triggered by mechanisms able to sense specific metabolic-changed danger signals and control the secretion of proinflammatory cytokines such as IL-1β and IL-18 in this aberrant proinflammatory response [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic proinflammatory cytokines are considered to be pathologic mediators of diabetogenic metabolic disorders, associated with insulin resistance and pancreatic islet cell death [8][9][10]21,22]. Recent studies have shown the participation of inflammasome complexes triggered by mechanisms able to sense specific metabolic-changed danger signals and control the secretion of proinflammatory cytokines such as IL-1β and IL-18 in this aberrant proinflammatory response [23].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the maternal environment have received particular attention in the last decades as they can program permanent effects on the fetal physiology and metabolism. This fetal programming may result from different stimuli throughout pregnancy or at specific periods and increases the prevalence of coronary heart disease and diabetes, among many other conditions during adulthood [9]. Metabolic adaptations to fail or excess the fetal nutritional demand (as for glucose in diabetic pregnancies), stress, chronic and acute inflammation are some of the aspects that are being studied [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood obesity is a significant risk factor for diabetes (Bacha & Gidding, ), respiratory problems (Mohanan, Tapp, McWilliams, & Dulin, ), cardiovascular dysfunction (Cote, Harris, Panagiotopoulos, Sandor, & Devlin, ), and poor psychological health (Beck, ). Childhood obesity also tracks to adulthood, leading to an increased risk of later morbidity and mortality (Maffeis & Tato, ).…”
Section: Introductionmentioning
confidence: 99%
“…[8] According to Bacha, longitudinal studies in adults show that obesity is a risk factor for coronary heart disease and heart failure; an increment of 1 unit of body mass index increases the risk by 5% for men and 7% for women. [9] Adipose tissue is surrounded by an extensive capillary network, and after a meal, the adipose tissue blood flow increases. Adipose tissue is what makes up a majority of the total body weight, and a big amount of fluid can be seen in the interstitial space of the Section: Medicine adipose tissue.…”
Section: Introductionmentioning
confidence: 99%